Changing Trends in Firework-Related Eye Injuries in Southern China: A 5-Year Retrospective Study of 468 Cases. (7th August 2020) - Wang, Fangyu; Lou, Bingsheng; Jiang, Zhaoxin; Yang, Yao; Ma, Xinqi; Lin, Xiaofeng
Abstract : Firework-related eye injury is a horrible medical problem and creates huge health and social burdens. Herein, we explored the changing trends and demographic and clinical features of firework-related eye injury, in an effort to inform strategies to prevent this injury. We reviewed the data of 468 hospitalized patients who underwent surgery for firework-related eye injury at the Zhongshan Ophthalmic Center between January 2013 and December 2017. During this period, the trend in firework-related eye injuries was stable (mean, 93 ± 14 cases per year), and fireworks were the major cause of explosive eye injury. The average age of the patients was 24 ± 18 years and 87% of the patients were male, with boys under 10 years of age comprising the largest group (27% of patients). There were an average of 24 ± 7 cases per year from urban areas and 70 ± 8 cases from rural areas (P < 0.05 ). Furthermore, 21 ± 5% of cases occurred during Spring Festival. After treatment, the best corrected visual acuity was increased compared to that before treatment, and the intraocular pressure tended to become normal by the final visit (P < 0.05 ). The top three diagnoses were cataract (39%), retinal detachment (18%), and choroidal detachment (14%). Additionally, the most common surgery was cataract extraction (25%), followed by pars plana vitrectomy (19%) and pars plana vitrectomy plus pars plana lensectomy (10%). Over the five-year study period, day surgery hospitalization increased from 1% to 32%. This was associated with a corresponding decrease in the length of hospitalization, without adverse events, demonstrating that day surgery is feasible in firework-related eye injury cases. The present study results suggest that greater attention should be paid to firework-related eye injury, and a variety of measures should be taken to prevent this kind of ocular tragedy.